Octadecylpropyl Sulfamide Reduces Neurodegeneration and Restores the Memory Deficits Induced by Hypoxia-Ischemia in Mice - Kossatz, Elk; Silva-Peña, Daniel; Suárez, Juan; de Fonseca, Fernando R.; Maldonado, Rafael; Robledo, Patricia (Frontiers in Pharmacology, 2018)
The PPAR-α agonist, oleoylethanolamide (OEA) has neuroprotective properties in stroke models. However, its rapid degradation represents a limitation for an effective therapeutic approach. In this study, we evaluated the effects of a stable OEA-modelled compound, octadecylpropyl sulfamide (SUL) on the cognitive, behavioral, cellular and molecular alterations associated with hypoxia-ischemia (HI) in mice. Mice subjected to HI were treated with the PPAR-α antagonist GW6471 (GW) (1 mg/kg) followed 15 min later by SUL (3, 10 mg/kg). Behavioral, motor, and cognitive tests were carried out 24 h and 7 days after the HI. The levels of microglia, reactive astrocytes and neuronal nuclei were studied using immunofluorescence, and the expression of genes related to the N-acylethanolamides/endocannabinoid signaling systems was determined by qRT-PCR at the end of the experimental sequence. HI induced brain damage in the ipsilateral hippocampus and cortex, which lead to severe memory impairments, and motor coordination deficits. Significant neuronal loss, increased microglia and reactive astrocytes, and compensatory changes in genes associated with the inflammation/immune and endocannabinoid systems were observed in these brain structures of lesioned mice. SUL reversed the memory and motor deficits, decreased the overexpression of microglia and astrocytes, and reduced neurodegeneration induced by HI. Cnr1 and Cnr2 gene expression was modulated by SUL in both sham and HI mice, while Pparα and Faah expression was regulated in HI mice. GW completely blocked the beneficial actions of SUL. These findings suggest that treatment with SUL reduces brain damage and the associated motor and memory deficits induced by HI probably by normalizing the changes in neuroinflammation/immune system mediators.